Fabry disease associated with chronic meningitis and cerebral infarction. Issue 4 (27th January 2015) - Yanagimura, Fumihiro; Fukushima, Takao; Sakamaki, Yuichi; Nakamura, Gen; Maruyama, Hiroki; Makino, Kunihiko
Abstract A 48‐year‐old man receiving enzyme replacement therapy for Fabry disease was admitted to Niigata Prefectural Shibata Hospital, Shibata, Japan, for a fever, headache, dysarthria and right hemiparesis. Aseptic meningitis and lacunar infarction were diagnosed, and symptomatic therapy and antiplatelet therapy improved the symptoms. As he had had a sub‐ever and headache once a month for 1 year, and developed a fever and headache again 2 months after discharge from our hospital, chronic meningitis was diagnosed. Prednisolone was introduced, and there was no relapse of meningitis thereafter. It is hypothesized that glycosphingolipids accumulated at the leptomeninges could induce aseptic meningitis and result in a shift to chronic meningitis. Chronic meningitis is implicated as the cause of a chronic headache in Fabry disease, and steroids could be a potential effective therapy.